Quantifying bimolecular recombination losses in organic bulk heterojunction solar cells - Koster, L. Jan Anton; Kemerink, Martijn; Wienk, Martinus Maria; Maturová, Klára; Janssen, René A. J. (Advanced materials, 2011)
We present a new experimental technique that affords direct quantification of the fraction of charge carriers lost in poly(3-hexylthiophene):fullerene solar cells by bimolecular recombination. Depending on annealing conditions up to 17% of carriers recombine bimolecularly under solar illumination. We explain our findings with a closed analytical expression for the photocurrent generated by an organic solar cell.